(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2008)
Sartre’s brilliant and indefatigable investigations of consciousness are less well read than they used to be. But the advent of positron emission tomography, functional magnetic resonance imaging, and magnetoencephalography has enabled neuroscientist to look at the functioning brain during tasks requiring consciousness, and they are ratifying many of the insights that Sartre obtained from phenomenology. This paper reviews these, and introduces a self-propelling, flock living machine as an illustration of them, and of the basics of being human that Sartre set out, principally in the early phase of his career culminating in ’Being and Nothingness’.